Modelling sustainability and the role of deliberative democracy - Hartz-Karp, Janette; Marinova, Dora (The Modelling and Simulation Society of Australia and New Zealand Inc., 2011)
Given the strong inertia of preconceived ideas about the role of ordinary citizens, it is not surprising that deliberative democracy has been invisible to most sustainability modellers. If modelling is a way of copying how a system works in real life, then the traditional modelling approaches to sustainability, grounded in particular disciplines, often based on economic rationalism and relatively short-term horizons, will be inadequate. Modelling that is more holistic and resilient (capable of adaptation) will need to include the values and viewpoints of ordinary people, as well as collaborative problem solving, policy development, decision-making, action and continual monitoring. The paper analyses several case studies which have used deliberative democracy techniques to create models for urban development planning in Western Australia. It concludes that deliberative democracy can provide a different way to the development of models and communities which are not only more sustainable but also more resilient to the unpredictability of the future.